KARAKTERISTIK MARSHALL CAMPURAN HOT ROLLED SHEET WEARING COURSE MENGGUNAKAN BAHAN TAMBAH PLASTIK BEKAS JENIS POLYETHYLENE TEREPHTHALATE - Yusrizal Yahya; Desriantomy .; Robby . (Jurnal Transportasi, 2019)
Abstract This study was conducted to determine the benefits of the use of polyethylene terephthalate used plastic as additives in hot asphalt mixture Hot Rolled Sheet Wearing Course. Marshall testing was carried out on specimens using polyethylene terephthalate plastic additives, with variations in the ingredients added 2%, 4%, 6%, 8%, and 10% to the weight of asphalt on specimens with Optimum Asphalt Content. Marshall parameters of test specimens generally meet the existing specifications, except the Void In Mixture value for specimens with plastic content of 8% and 10%. The optimum plastic content obtained from this study is 7.80%. Keywords: asphalt mixture, hot rolled sheet, Marshall parameters, polyethylene terephthalate  Abstrak Studi ini dilakukan untuk mengetahui manfaat penggunaan plastik bekas jenis Polyethylene Terephthalate sebagai bahan tambah pada campuran beraspal panas jenis Hot Rolled Sheet Wearing Course. Pengujian Marshall dilakukan terhadap benda-benda uji yang menggunakan bahan tambah plastik jenis Polyethylene Terephthalate, dengan variasi bahan tambah 2%, 4%, 6%, 8%, dan 10% terhadap berat aspal pada benda uji dengan Kadar Aspal Optimum. Parameter Marshall benda-benda uji umumnya memenuhi spesifikasi yang ada, kecuali nilai Void In Mixture untuk benda-benda uji dengan kadar plastik 8% dan 10%. Kadar plastik optimum yang diperoleh dari studi ini adalah 7,80%. Kata-kata kunci: campuran beraspal, hot rolled sheet, parameter Marshall, polyethylene terephthalate